Mycosphaerella and Teratosphaeria species associated with leaf diseases on Eucalyptus globulus in southern Brazil - TEODORO, Marcela; FERREIRA, Maria; GUIMARÃES, Lúcio; MAFIA, Reginaldo; GROENEWALD, Johannes; CROUS, Pedro; ALFENAS, Acelino (Phytopathologia Mediterranea, 2012)
Leaf blight and defoliation caused by Teratosphaeria species is one of the most important leaf diseases of Eucalyptus globulus. Due to the importance of this tree species for the production of pulp and paper, and recent reports of severe leaf disease symptoms in Brazil, the present study was conducted to identify the pathogen(s) involved. Symptomatic leaves were collected in the Brazilian states of Paraná and Rio Grande do Sul, single ascospore cultures established, and isolates were investigated using DNA-based molecular tools. A species-specific PCR and sequence data from the nuclear ribosomal DNA operon were used for species identification. The following seven species were identified: Mycosphaerella scytalidii, Dissoconium dekkeri (=M. lateralis), Teratosphaeria ohnowa, T. perpendicularis, T. pseudafricana, T. flexuosa and T.nubilosa. Of the recorded species, T. nubilosa is regarded as the most serious threat to the cultivation of E. globulus in the states surveyed.